Muslim Consumers’ Perceptions of Halal Certified Make Over Products in Surabaya - Zakiya Jihan Salsabila; Nikmatus Safar Mardiah (ASEAN Journal of Halal Study, 2024)
This study aims to analyse Muslim consumers’ perceptions of halal-certified Make Over cosmetic products in Surabaya. The research method used is descriptive qualitative with data collection techniques through semi structured interviews with Muslim consumers who buy Make Over products at Jelita Cosmetic Surabaya store. The results showed that Muslim consumers have a positive perception of halal certification on Make Over products, but there are still some misconceptions and lack of awareness of the importance of halal cosmetics. Factors that influence consumer perceptions include knowledge of halal ingredients and production processes, product quality, and brand image. This study provides insights for halal cosmetics manufacturers in improving the education and marketing of their products to Muslim consumers. Further efforts are needed to increase Muslim consumers’ awareness and understanding of the urgency of using halal-certified cosmetics.